Phlebitis of the left internal saphenous vein - Feblotrombosis iliac femoro - pulmonary embolism infarction - elebotomy - aspiration of the clots of the external iliac - resection of the femoral vein - healing - Suiffet, Walter; Musso, Romeo (Cirugía del Uruguay, 2020)
Presented at session 1st November 1944